A new fern species of Christella (Thelypteridaceae) from India - Behera, Sandip Kumar; Kushwaha, Arun Kumar; Khare, Prem Behari; Barik, Saroj Kanta (Phytotaxa, 2019)
A new fern species Christella kendujharensis (family Thelypteridaceae) from Odisha, India is described and illustrated. It shows morphological resemblance with Christella clarkei (Bedd.) C.F. Reed. While C. kendujharensis has ascending rhizome, reduced lower pinnae and irregular shaped pinnules, C. clarkei has creeping rhizome, non-reduced lower pinnae and regular shaped pinnules. Based on IUCN criteria (ver3.1), the new species is assessed as Critically Endangered (CR) B2abC2a(i)D.